PENGGUNAAN MEDIA PUZZLE UNTUK MENINGKATKAN KEMAMPUAN LITERASI MEMBACA SISWA KELAS II DI SD NEGERI 1 LAMBHEU ACEH BESAR - Winda Asnita; Aida Fitri; Hasniyati; Rahmat Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The lack of use of creative and interesting learning media is the cause of the low reading literacy skills of students in grade II of SD Negeri 1 Lambheu, Aceh Besar Regency. Reading literacy skills are one of the basic skills that students must have to be able to continue the next learning process. To address the problem, Puzzle media is implemented to make learning more engaging, enjoyable, and student-centered. This study aims to describe teacher activities, student activities, and to determine the improvement of students' reading literacy skills through the use of Puzzle media. The method used is classroom action research (CAR) which was carried out in two cycles, involving 29 students. Data were collected through observation and tests, and analyzed descriptively qualitatively with a percentage formula. The results of the study showed a significant increase in teacher activity, in cycle I obtained a average of 71,87% (very good) in cycle II obtained a average of 87,5%. Student activity also increased from 67,89% (good) in cycle I to 73,28% ( good) in cycle II. Students' Reading literacy skills increased with a classical achievement of 75.86% in cycle I, and with a classical achievement of 82.75% in cycle II. This increase indicates that the use of Puzzle media is effective in improving students' reading literacy skills in grade II of SD Negeri 1 Lambheu, Aceh Besar Regency